Quality improvement of posyandu cadres in optimizing stunting prevention in toddlers and adolescent women - Arief Kusuma Wardani; Dhea Nur Hikmah; Selma Septi Pratiwi; Yanvi Adika Hikmareza; Sherli Febria Nurmalasari (Community Empowerment, 2023)
The huge number of stunted families is a major issue in Magelang, especially in Sidoagung Village. The community service program is aimed at improving the competency of cadres who serve as community assistants in developing public knowledge about the RDA for nutritional adequacy in pregnant women and young women. To address this issue, the community service program implemented a number of preventive and curative initiatives, including socialization through the distribution of educational posters, counseling on stunting for possible stunting cadres and families, and the enhancement of Posyandu services. The program has influence on developing competence in assisting the community, particularly in recognizing stunting and how to directly avoid it through the use of media posters, as well as understanding in supplying additional food based on nutritional adequacy.